Relationship Between The Level of Knowledge and Attitudes of Female Students at State Secondary School 2 Panyabungan - Aminanti, Essy (Cattleya Darmaya Fortuna, 2024)
Cysts are benign tumors that consist of sacs filled with fluid, air, pus, and other materials. Internal genital cysts can occur at any time between puberty and menopause, even during pregnancy. Knowledge and attitudes of adolescent girls are crucial because internal genital cysts are common in women. Dietary patterns also influence the development of internal genital cysts, and adolescent girls' attitudes also play a significant role, as negative attitudes toward internal genital cysts can negatively impact internal genital disease. This study aims to determine the relationship between knowledge and attitudes of adolescent girls regarding internal genital cysts. This research is a descriptive correlation study with a cross-sectional study approach. The data source in this study is primary data measured using an instrument in the form of a questionnaire. Data analysis using the Chi-Square correlation technique using the SPSS (Statistical Product and Service Solution) program. The sample in this study was stratified random sampling, namely taking samples in groups from the entire population of female adolescents regarding internal genital cysts at SMP Negeri 2 Panyabungan with a sample of 92 people. Based on the table of research results on the relationship between knowledge and attitudes of female adolescents regarding internal genital cysts, the calculated X2 value is 14.899 > X2 table, which is 5.591 with a df value of 2. The sig value is 0.00, which means that the p value is <0.01, so Ho is rejected and H1 is accepted. This means that